PEMBERDAYAAN PETANI PEMBUATAN KOMPOS HAYATI METANKOS DAN BIOPESTISIDA PENGENDALI HAMA PADI DI DESA PULAU RAMBAI KECAMATAN KAMPA KABUPATEN KAMPAR: Kompos hayati metankos dan biopestisida - Fauzana, Hafiz; Nelvia, Nelvia; Rustam, Rusli; AR, Arman Effendi; Erawati, Netti; Kurnia, Rita; Irfandri, Irfandri; Fitriana, Melani; Putri, Afra Fadhila; Yobi, Afrila (Jurnal Hilirisasi IPTEKS, 2024)
Pulau Rambai Village in Kampa Sub-district, Kampar District is one of the rice production centers. The rice planting for the 2023 planting period failed to harvest due to pests. The solution offered is the use of metankos biological compost and pest control using biopesticides. The purpose of this service activity is the solution offered is the use of metankos biological compost and pest control using biopesticides. The purpose of the service activity is to increase knowledge, skills and empower farmers in making metankos biological compost and biopesticides. The activity methods used are survey, consolidation, counseling, practice and empowerment. The measuring tool for the achievement of service activities is the knowledge and skills of farmers, the method is by distributing questionnaires before and after service activities so that a percentage increase is obtained. Farmers can practice and carry out the service activities that are advised, the level of success is measured by the percentage of farmers who carry it out. Empowerment activities in the form of practice and application of biological compost and biopesticides directly to plants every week through Kukerta students. The service activity was carried out at the Pulau Rambai Village Musholla on Thursday, July 25, 2024. The results of the service activities were an increase in farmers' knowledge of controlling rice pests using biopesticides by 56%, before counseling 100% of farmers had never used biopesticides. Farmers practiced the activities that were suggested in the form of control using biological agents Metarhizum sp and making metankos biological compost was 27.5%. The conclusion of the service activity is that the counseling and empowerment carried out succeeded in increasing farmers' knowledge and empowerment regarding the manufacture of metankos biological compost and biopesticides